A New look on the Oxidation Process of Sodium Sulfite - F.R. Fouda, Mohammad; I. Saleh, Hesham; M. Abd- Elzaher, Mokhles (Asian Journal of Chemistry, 2012)
The article present a new mechanism, suggested for the oxidation process of solid sodium sulfite. The process was found to proceed via four thermal decomposition steps. The first of them (257-318 ºC) is characterized by formation of sodium pentasulfate, Na2O•5SO3 (which was not detected before by any investigator) and sodium metal which oxidized to Na2O and NaO2 during the second step (318-640 ºC). The third step (645-790 ºC) is characterized by formation of sodium sulfate and sulfurdioxide. The first and second compounds are formed as a result of thermal dissociation of sodium at ca. 600 ºC, whereas the first and ones are produced as a result of interaction of sodium sulfide and sulfur trioxide resulted from dissociation of sodium pentasulfate at ca. 700 ºC. The liberated sulfur oxides (SO2 and SO3) reacted with sodium oxides leading to the formation of Na2SO4 and Na2SO3 during the fourth step (> 790 ºC). The further fate of the newly formed species of sulfite is the same as described before, so that it was found experimentally that the percentages of the sulfite salt in the decrease gradually above 700 ºC and reaches about 0.1 % at 1000 ºC.